Multi-K KNN regression with bootstrap aggregation: Accurate predictions and alternative prediction intervals - Sriprasert, Soraida; Srisuradetchai, Patchanok (Edelweiss Applied Science and Technology, 2025)
The k-nearest neighbors (KNN) algorithm is widely recognized for its simplicity and flexibility in modeling complex, non-linear relationships; however, standard KNN regression does not inherently provide prediction intervals (PIs), presenting a persistent challenge for uncertainty quantification. This study introduces a bootstrap-based multi-K approach specifically designed to construct robust prediction intervals in KNN regression. By systematically aggregating predictions across multiple neighborhood sizes through ensemble techniques and bootstrap resampling, the method effectively quantifies prediction uncertainty, particularly in challenging high-dimensional scenarios. Evaluations conducted on 15 diverse datasets spanning education, healthcare, chemistry, economics, and social sciences reveal that the proposed approach consistently achieves competitive predictive accuracy compared to traditional regression methods. Although traditional regression produces wider intervals with higher coverage probabilities, the proposed bootstrap-based KNN method generates notably tighter intervals, enhancing interpretability and practical utility. Despite occasionally reduced coverage probabilities, especially in high-dimensional contexts, the proposed methodology effectively balances precision and predictive coverage. Practically, this multi-K bootstrap approach provides researchers and practitioners with an effective and interpretable method for robust uncertainty quantification in complex predictive modeling tasks.